New Pedagogical Approaches to Induce Sustainable Development Goals - Jose Carlos Quadrado; Kseniya K. Zaitseva (Moscow Polytechnic University, 2019)
High quality professional training in accordance with the principles of outcome-based approach depends on the learning outcomes students are expected to achieve upon graduation from the educational program. However, the definition of a set of core competencies is just one of the steps that have to be fulfilled, but not enough for successful achievement of intended learning outcomes by the students. The paper considers the role of teaching and learning methods in designing and implementing of educational programs.Flipped Learning is becoming a well-known pedagogical approach in which direct instruction moves consistently from the group learning space to the individual learning space, and the resulting group space is transformed into a dynamic, interactive learning environment where the educator guides students as they apply concepts and engage creatively in the subject matter.Education of the next generation of practitioners that will creatively implement the Sustainable Development Goals (SDG's) by 2030 requires the complete rethinking by the educator how to do the job being done on a certain way for years. The flipped classroom model addresses how students learn best and become more engaged. Discussions and hands-on activities tend to keep students' interest. While educators work with students directly as they explore the concepts they're learning in class, they can provide immediate feedback that helps students improve their learning as they go.The students pursuing the SDG's creative engagement in classrooms become better at taking the lead on finding valuable resources and pursuing learning their own way using the flipped learning. This approach explores a specific challenge in the development of education and practice.